Asset liability management optimisation : a practitioner's guide to balance sheet management and remodelling - Lubinska, Beata, 1973- (Wiley finance series., 2020)
"The role of the Asset Liability Management function (ALM) in the management of the banking book of a bank is constantly growing. A clear evolution can be seen as ALM mangers realise that reactive approach, which consists in the management of the banking book as a passive structure resulting from the commercial and funding strategy of a bank, should be replaced by proactive approach where the banking book structure is decided in a conscious and active way in order to come up with the desired target structure of the banking book. This book is meant to promote a change in the role of ALM and, in general, in the approach towards financial risk management practice in the modern finance. It is going to show that proactive role of ALM through integrated approach for management of two main financial risk categories, i.e. interest rate risk and liquidity risk under one approach and interrelation with the commercial strategy which a bank wants to adopt, brings significant benefits. Those benefits are mainly economical and can be quantified. The need for change seems to be driven by a number of challenges, such as heavily regulated landscape, low or negative rates (in Eurozone) and margin compression, which the banking industry is facing since 2008"--